2001
DOI: 10.1021/nl015566f
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Bonded Organic Monolayers on a Carbon Substrate:  A New Paradigm for Molecular Electronics

Abstract: We report herein the fabrication of a molecular junction in which a thin (8−15 Å) layer of oriented organic molecules is positioned between two electronic conductors. The molecular layer becomes a component in an electronic circuit and exhibits properties that depend strongly on molecular structure. Bonding between the carbon substrate and the molecular layer is covalent and conjugated, and thus differs fundamentally from that of the widely studied self-assembled monolayers of alkane thiols on metal surfaces. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 29 publications
2
116
0
Order By: Relevance
“…The use of mercury in these junctions is also similar to the Hg Á/Ag junctions described by Whitesides and coworkers [4,5] to the Hg Á/ SiO 2 Á/p-Si junctions of Cahen and coworkers [6] and to Hg Á/C junctions reported recently by McCreery and coworkers [7] An overview of the related research with scanning probe microscopy can be found in a recent report by Bard and co-workers [8]. In this report, in order to improve the stability of the junctions and reproducibility of the resulting I/V curves, we first characterize the structure of the alkanethiol monolayers on gold substrates by recording standard cyclic voltammetric current voltage curves in aqueous electrolytes of a redox probe.…”
Section: Introductionsupporting
confidence: 78%
“…The use of mercury in these junctions is also similar to the Hg Á/Ag junctions described by Whitesides and coworkers [4,5] to the Hg Á/ SiO 2 Á/p-Si junctions of Cahen and coworkers [6] and to Hg Á/C junctions reported recently by McCreery and coworkers [7] An overview of the related research with scanning probe microscopy can be found in a recent report by Bard and co-workers [8]. In this report, in order to improve the stability of the junctions and reproducibility of the resulting I/V curves, we first characterize the structure of the alkanethiol monolayers on gold substrates by recording standard cyclic voltammetric current voltage curves in aqueous electrolytes of a redox probe.…”
Section: Introductionsupporting
confidence: 78%
“…In order to investigate if this range of barrier heights is realized in carbon/molecule devices, large area PPF/molecule/Cu molecular junctions were constructed from the structures in Fig. 2 using previously described techniques (15,(17)(18)(19). In all cases, the value of the attenuation factor (β) was measured by variation of the molecular layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Although each method has certain advantages and disadvantages, it is clear that the entire system must be considered in order to delineate the main factors influencing molecular conduction. Whereas many groups employ thiolate-based self-assembled monolayers (SAMs) on metallic substrates as a base system, we have taken an alternative approach using carbon electrodes (6,(14)(15)(16)(17)(18)(19). The foundation of this paradigm is a flat carbon electrode composed of pyrolyzed photoresist films (PPF) with covalently bonded nanoscopic molecular layers deposited using the electrochemical reduction of diazonium reagents.…”
mentioning
confidence: 99%
“…Graphitic carbons have many attractive characteristics, including ease-ofhandling, low-cost, high mechanical stability and good electrical conductivity. The material is readily available in a number of forms including high surface area felts and cloths suitable as supports for combinatorial chemistry [1,2], carbon powders useful for chromatography [3], glassy carbon (GC) [4], a convenient material for planar electrodes and very smooth films of pyrolysed photoresist [5] suitable for applications in molecular electronics [6,7,8]. Another advantage of graphitic carbon is that the surface can be easily modified by methods which give very stable molecular coatings, attached by strong C-C [9] or C-N covalent bonds.…”
Section: Introductionmentioning
confidence: 99%